Valorando los recursos naturales y su incorporación en las cuentas nacionales: el caso minero peruano - Orihuela Romero, Carlos (2004)
This study uses the net price method to estimate the depreciation of natural capital and the true net national product of the Peru’s mining sector during the 1992-2001 period. The estimations show that approximately 38% of the Peru’s annual mining income recorded by its national account system corresponds to the depreciation of its natural resources and, therefore, it does not represent the true economic income. This loss of natural capital was widely greater than the payment realized by the government through the «Canon Minero». For this reason, the re-investment of the resource rent from the mining sector was smaller than the loss of natural capital, which implies that the Hartwick’s rule was not achieved for the case of the Peru’s mining sector, at least during the period in study.